Biweekly cisplatin and gemcitabine in patients with advanced biliary tract cancer. Issue 8 (17th November 2017) - Ahn, Daniel H.; Reardon, Josh; Ahn, Chul W.; Bupathi, Manojkumar; Mikhail, Sameh; Wu, Christina Sing‐Ying; Bekaii‐Saab, Tanios
Abstract : Treatment with cisplatin and gemcitabine demonstrates a survival benefit in patients with advanced biliary tract cancer (ABTC). However, the weekly administration can add significant toxicities that may prohibit prolonged treatment. Based on previous studies, we implemented a modified biweekly regimen of GC in an attempt to optimize the prescribed regimen with an improved toxicity profile, added convenience to patients while maintaining efficacy. Patients with ABTC were treated with fixed dose rate (FDR) gemcitabine (1, 000 mg/m 2 /min) and cisplatin 20 mg/m 2 on days 1 and 15 of every 28‐day cycle. Patients received treatment until time of progression, death, or discontinuation due to intolerance. Collected data included demographics, clinico‐pathologic features, toxicities, and survival. Kaplan‐Meier curves were used to calculate the median overall survival (OS) and progression free survival (PFS). The study included 107 evaluable pts with unresectable ABTC who received the biweekly regimen. Sites of tumor included gallbladder (21.5%), ampullary (3.7%), and bile duct (74.8%). Median number of cycles was 6 (1–27). Median PFS was 8.34 (6.74, 9.23) months and median OS was 10.32 (9.10, 11.43) months. Most common grade ≥3 adverse events included neutropenia (11%), fatigue (10%), and thrombocytopenia (6.4%). Biweekly FDR GC in ABTC is associated with a more favorable toxicity profile while maintaining efficacy similar to that observed in prior clinical trials. Minimal toxicities were observed despite a prolonged course for many patients. Further prospective trials should consider evaluating the role of biweekly GC regimen in ABTC, including a potentially more favorable platform in novel experimental strategies. Abstract : What's new? Patients diagnosed with biliary tract cancer frequently present with advanced or metastatic disease, for which standard treatment entails an eight‐week‐long course of weekly administration of combined gemcitabine‐cisplatin (GC) chemotherapy. Here, a modified biweekly regimen of GC chemotherapy was examined as a means of potentially optimizing treatment for advanced biliary cancer. Despite a prolonged treatment course, with a median of six biweekly treatment cycles, the modified regimen was associated with minimal toxicities. Median overall survival was just over 10 months. The findings suggest that biweekly GC administration can reduce treatment‐related toxicities, while maintaining clinical efficacy and allowing for continued treatment.